Mapping rehabilitation pathways after cardiac surgery: Identifying key points for patient involvement and gaps in care - Bente Skovsby Toft; Hilary Louise Bekker; Lotte Ørneborg Rodkjær; Ivy Susanne Modrau (PLoS ONE, 2025)
Background Cardiac rehabilitation in Denmark is cross-sectional and decentralised to municipalities, resulting in different pathways and practices. A comprehensive overview of these variations and their impact on the rehabilitation process following cardiac surgery is lacking. Aim This study aims to map the rehabilitation pathways after cardiac surgery, and to identify key interactions between patients and clinicians that influence rehabilitation outcomes and patient experiences. Methods A qualitative multi-method study was conducted using metro mapping methods, including document analysis, stakeholder consultations, practice observations and go-along interviews across multiple sites in Central and Northern Denmark Regions. Results Mapping revealed significant variability in cardiac rehabilitation pathways across healthcare settings, including diverse referral, enrolment, content, delivery methods, and follow-up procedures, involving multiple clinicians. A consistent finding across all pathways was both a prolonged transition from in-hospital phase 1 to outpatient phase 2 rehabilitation, resulting in a gap of care, and minimal patient involvement in decision-making and planning during the early phase of recovery. Conclusion This study provides a comprehensive overview of current rehabilitation pathways following cardiac surgery, revealing significant variability and challenges. Our findings emphasise the need for a person-centred redesign of the cardiac rehabilitation pathway with improved sector transitions. Our findings provide guidance for clinicians and underscore the importance of clear legal frameworks, consistent guidelines, and co-design of cardiac rehabilitation programmes with patients. Strengthening these areas could promote greater patient engagement, reduce variability in service delivery, and ultimately lead to better patient outcomes and experiences.